Desulfurization and dehydration catalyst as well as preparation method and application thereof

Through a new method of preparation of desulfurization and dehydration catalysts, modified clay and alumina are used to form catalysts with microporous and mesoporous structures, solving the problems of cumbersome desulfurization and dehydration processes and unsatisfactory effects in the prior art, and achieving simple and economical catalyst preparation and efficient desulfurization and dehydration effects.

CN119793469APending Publication Date: 2025-04-11SHENYANG SANJUKAITE CATALYST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411791885.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the use process of desulfurization and dehydration catalysts is complicated, the effect is not ideal, and complex proportions and cumbersome operations of the two catalysts are required.

Method used

A new method of preparation of desulfurization and dehydration catalyst is adopted to obtain modified clay by mixing and calculating alkaline substances and clay, and then reacting with alumina and soluble transition metal salts to form a silicon-aluminum precursor. After steps such as aging, crystallization and granulation, a catalyst with microporous and mesoporous structure is prepared.

Benefits of technology

It realizes the simultaneous removal of water and sulfides, which has the advantages of simple preparation, low cost and convenient use, and avoids complex catalyst ratios and cumbersome operation problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793469A_ABST
    Figure CN119793469A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and particularly relates to a desulfurization and dehydration catalyst and a preparation method and application thereof. The preparation method comprises the following steps: S1, mixing an alkaline substance and clay, and roasting to obtain modified clay; s2, mixing alkali liquor, aluminum oxide and modified clay, reacting to obtain a silicon-aluminum precursor, adding soluble transition metal salt, aging, crystallizing, and carrying out solid-liquid separation to obtain a wet product; s3, mixing aluminum oxide and an alkaline substance to obtain modified aluminum oxide; and S4, mixing the modified aluminum oxide, the wet product and an auxiliary agent, granulating, drying and roasting to obtain the desulfurization and dehydration catalyst. The obtained desulfurization and dehydration catalyst has microporous and mesoporous structures at the same time, can remove water and sulfides at the same time, and has the advantages of simple preparation and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a desulfurization and dehydration catalyst and a preparation method and application thereof. Background Art

[0002] In the chemical industry, when preparing propylene, the materials flowing out of the reaction will contain sulfide and water, among which sulfide mostly exists in the form of hydrogen sulfide. Hydrogen sulfide gas is a toxic and harmful gas. Untreated discharge will cause environmental pollution; when the hydrogen sulfide gas in the air reaches a certain concentration, it will also cause people to have symptoms such as dizziness and headache, and in severe cases it will threaten people's life and health. In the subsequent process of propylene treatment, sulfide will corrode the pipeline and affect the subsequent process. Therefore, the propylene obtained must be free of hydrogen sulfide. At the same time, because the subsequent treatment process of propylene has certain requirements for its water content, the most ideal treatment method is to remove sulfide and water at the same time. In the prior art, the method of using two catalysts in series is generally adopted to achieve the effect of simultaneous desulfurization and dehydration, and in order to meet the two removal accuracies, the performance and matching methods of the two catalysts are strictly required. Because there is a certain gap in the bulk density, strength, active components, etc. of the two catalysts, in the actual process of catalyst application, there are many factors to be considered in the process of formulating the grading scheme, and it is also necessary to adjust at any time according to different working conditions. At the same time, the use of two catalysts together is prone to the risk of catalyst breakage, so the catalyst loading process is more stringent; and when regenerating, the two catalysts may need to be regenerated separately, which is cumbersome. Therefore, the most ideal treatment method is to use one catalyst to achieve the effects of desulfurization and dehydration at the same time, so as to avoid complex calculation ratios and cumbersome operations. Summary of the invention

[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the desulfurization and dehydration catalysts used in the prior art, such as complicated steps in use and unsatisfactory desulfurization and dehydration effects, thereby providing a low-cost desulfurization and dehydration catalyst and its preparation method and application.

[0004] To this end, the present invention provides the following technical solutions.

[0005] The invention provides a preparation method of a desulfurization and dehydration catalyst, comprising the following steps: S1: mixing alkaline substances and clay, and calcining to obtain modified clay; S2: mixing alkali solution, alumina and modified clay, reacting, adding soluble transition metal salt to the obtained silicon-alumina precursor, aging, crystallizing, and solid-liquid separation to obtain a wet product; S3: mixing alumina and alkaline substances to obtain modified alumina; S4: mixing the modified alumina, the wet product and an additive, granulating, drying and calcining to obtain the desulfurization and dehydration catalyst.

[0006] Optionally, in S1, the calcination temperature is 300-400° C. and the calcination time is 2-3 hours.

[0007] Optionally, in S2, the reaction temperature is 60-80° C. and the reaction time is 2-4 hours.

[0008] Optionally, in S2, the reaction is carried out under stirring.

[0009] Optionally, in S2, the aging temperature is 60-80° C. and the time is 4-6 hours.

[0010] Optionally, in S2, the crystallization temperature is 80-100° C. and the time is 12-20 hours.

[0011] Optionally, in S4, the drying temperature is 90-120° C. and the drying time is 2-3 hours.

[0012] Optionally, in S4, the calcination temperature is 350-400° C. and the calcination time is 2-4 hours.

[0013] In the preparation method provided by the present invention, typically but not limitedly, the wet product obtained in S2 needs to be washed to neutrality.

[0014] Optionally, in S1, the mass ratio of clay to alkaline substance is 5:1 to 7:1.

[0015] Optionally, in S2, the molar ratio of silicon to aluminum in the silicon-aluminum precursor is 1:0.9 to 1.1.

[0016] Optionally, the liquid-to-solid volume mass ratio of the alkali solution to the clay is 1 mL: 0.9-1.1 g; optionally, the concentration of the alkali solution is 1-5 mol / L.

[0017] Optionally, in S3, the mass ratio of aluminum oxide to alkaline substance is 9:1 to 15:1.

[0018] Optionally, in S4, the mass ratio of modified alumina to wet product is 1:1-3.

[0019] Optionally, the mass of the soluble transition metal accounts for 3% to 6% of the mass of the desulfurization and dehydration catalyst.

[0020] Optionally, the mass of the auxiliary agent is 4% to 17% of the mass of the modified alumina.

[0021] Optionally, the granulation method includes ball forming.

[0022] In the preparation method provided by the present invention, typically but not limitedly, the dryness and wetness of the material need to be adjusted during the rolling ball forming, specifically, water can be added to the material in small amounts and multiple times until the moisture content of the material is 20% to 40%, and the spheres are ground against each other during the forming process to ensure that the surface of the spheres is smooth. The amount of water added is controlled so that the individual spheres do not stick to each other.

[0023] Optionally, the clay includes at least one of bentonite, kaolin, montmorillonite, diatomaceous earth and attapulgite.

[0024] Optionally, the alkaline substance includes at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate.

[0025] Optionally, the alkali solution includes at least one of sodium hydroxide solution, sodium carbonate solution and sodium bicarbonate solution.

[0026] Optionally, the soluble transition metal salt includes at least one of copper nitrate, iron nitrate, cobalt nitrate, copper sulfate, iron sulfate, and cobalt sulfate.

[0027] Optionally, the auxiliary agent includes at least one of carboxymethyl cellulose, sesbania powder and grass powder.

[0028] Optionally, the alumina is macroporous alumina; Optionally, the pore volume of the macroporous alumina is ≥ 0.8 cm 3 / g, average pore size ≥10nm; Optionally, the pore volume of the macroporous alumina is 0.8cm 3 / g~1.2cm 3 / g, and the average pore size is 10-30nm.

[0029] The present invention provides a desulfurization and dehydration catalyst prepared by the above preparation method; optionally, the particle size of the desulfurization and dehydration catalyst is 1.5 to 5 mm.

[0030] The present invention also provides application of the above desulfurization and dehydration catalyst in a propylene preparation process.

[0031] The beneficial effects of the present invention are:

[0032] The present invention provides a method for preparing a desulfurization and dehydration catalyst, comprising the following steps: S1: mixing alkaline substances and clay, calcining to obtain modified clay; S2: mixing alkali solution, alumina and modified clay, reacting, taking the obtained silicon-alumina precursor, adding soluble transition metal salt, aging, crystallizing, solid-liquid separation, and obtaining a wet product; S3: mixing alumina and alkaline substances to obtain modified alumina; S4: mixing modified alumina, wet product and auxiliary agent, granulating, drying, calcining, and obtaining a desulfurization and dehydration catalyst. The obtained desulfurization and dehydration catalyst has microporous and mesoporous structures at the same time, can achieve the simultaneous removal of water and sulfide, and has the advantages of simple preparation, low cost and convenient use.

[0033] Clay has low cost and wide sources. It can be used as a silicon source after being mixed with alkaline substances and calcined. In S2, alkali solution, alumina, and modified clay are first mixed to obtain a silicon-aluminum precursor, and then a soluble transition metal salt is added, aged, and crystallized. During the preparation process, aluminum ions and part of silicon ions are dissolved, and anionic pore formers are formed in the presence of alkaline substances, and micropores can be formed without the need to add additional templates. Transition metal ion exchange is completed while generating a special Si-O-Al structure microporous material, which saves preparation steps and avoids the damage to the microporous structure that may be caused by transition metal ion exchange after the microporous structure is formed, and finally a stable transition metal modified silicon-aluminum microporous material is obtained, which is the wet product in the present invention. The microporous material has a large surface area and high activity, and has good thermal stability and high sintering resistance in a high temperature environment. Alumina has a rich pore structure. In S3, alkaline substances are used to modify alumina so that alkaline active centers are evenly distributed on the surface of alumina, providing active centers for the desulfurization reaction and improving the desulfurization accuracy. At the same time, some mesoporous and microporous alumina pores are formed to provide a dehydration environment. In S4, the modified alumina, wet product, and additives are mixed, granulated, dried, and roasted to finally obtain a desulfurization and dehydration catalyst. During the roasting, the additives are thermally decomposed. The mesoporous material (modified alumina) and microporous material (wet product) prepared previously are grafted by granulation. The mesopores in alumina and the transition metal-modified silicon-aluminum microporous material form a new microporous structure, and new stacking pores are also formed between the two materials, so that the number of pores is increased and evenly distributed. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1This is the pore size distribution diagram of the desulfurization and dehydration catalyst obtained in Example 1;

[0036] Figure 2 This is the pore size distribution diagram of the desulfurization and dehydration catalyst obtained in Comparative Example 2;

[0037] Figure 3 This is the TEM image of the desulfurization and dehydration catalyst obtained in Example 1. DETAILED DESCRIPTION

[0038] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0039] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0040] Experimental drugs:

[0041] Alumina powder: macroporous alumina with a pore volume of 0.8 cm 3 / g~1.2cm 3 / g, average pore size 10nm~30nm, purity 70%;

[0042] Kaolin: China Kaolin Co., Ltd.;

[0043] Bentonite: Beipiao Tiancheng Activated Clay Factory;

[0044] Montmorillonite: Beipiao Tiancheng Activated Clay Factory;

[0045] Diatomaceous earth: Shandong Yonglian New Material Technology Co., Ltd.;

[0046] Attapulgite: Mingguang Liyuan Mineral Co., Ltd.;

[0047] Sesbania powder: Henan Jiujin Technology Co., Ltd.;

[0048] Grass powder: Heze Xinhe Agricultural Development Co., Ltd.

[0049] Example 1

[0050] This embodiment provides a desulfurization and dehydration catalyst and a preparation method thereof, comprising the following steps:

[0051] (1) 50 g of sodium hydroxide and 300 g of kaolin were mixed and calcined at 350° C. for 2 h to obtain modified clay.

[0052] (2) 300 mL of 3 mol / L sodium hydroxide solution, 223 g of alumina powder, and the modified clay obtained in step (1) were mixed and stirred at 70° C. for 3 h to react. After the reaction, the obtained silicon-aluminum precursor (silicon-aluminum molar ratio of about 1:1) was placed in a constant temperature and humidity drying oven, 93.5 g of copper nitrate trihydrate was added, and aged at 70° C. for 5 h. The temperature was then raised to 90° C. for crystallization for 16 h, and filtered to obtain 499 g of a wet product, which was washed to neutrality.

[0053] (3) 286 g of alumina powder and 20 g of sodium hydroxide were mixed evenly to obtain modified alumina.

[0054] (4) The modified alumina, the wet product obtained in (2), and 18 g of grass powder (accounting for 8.17% of the mass of the modified alumina) were mixed, water was added to adjust the material moisture content to about 30%, and the mixture was rolled into balls, dried at 120° C. for 2 h, and calcined at 380° C. for 3 h to obtain a desulfurization and dehydration catalyst with a particle size of 2 to 3 mm. Among them, copper accounts for 4.12% of the mass of the desulfurization and dehydration catalyst.

[0055] Example 2

[0056] This embodiment provides a desulfurization and dehydration catalyst and a preparation method thereof, comprising the following steps:

[0057] (1) 50 g of sodium carbonate and 300 g of bentonite were mixed and calcined at 350°C for 2 h to obtain modified clay.

[0058] (2) 300 mL of 3 mol / L sodium hydroxide solution, 193 g of alumina powder, and the modified clay obtained in step (1) were mixed and stirred at 70° C. for 3 h to react. After the reaction, the obtained silicon-aluminum precursor (silicon-aluminum molar ratio of about 1:1) was placed in a constant temperature and humidity drying oven, 85.8 g of copper nitrate trihydrate was added, and the mixture was aged at 70° C. for 5 h, then heated to 90° C. for crystallization for 16 h, filtered, and 469 g of a wet product was obtained, which was washed to neutrality.

[0059] (3) 257 g of alumina powder and 18 g of sodium hydroxide were mixed evenly to obtain modified alumina.

[0060] (4) The modified alumina, the wet product obtained in (2), and 16.2 g of carboxymethyl cellulose (accounting for 8.19% of the mass of the modified alumina) were mixed, water was added to adjust the material moisture content to about 30%, and the mixture was rolled into balls, dried at 120° C. for 2 h, and calcined at 380° C. for 3 h to obtain a desulfurization and dehydration catalyst with a particle size of 2 to 3 mm. Among them, copper accounts for 4.20% of the mass of the desulfurization and dehydration catalyst.

[0061] Example 3

[0062] This embodiment provides a desulfurization and dehydration catalyst and a preparation method thereof, comprising the following steps:

[0063] (1) 50 g of sodium bicarbonate and 300 g of montmorillonite were mixed and calcined at 350°C for 2 h to obtain modified clay.

[0064] (2) 300 mL of 3 mol / L sodium hydroxide solution, 159 g of alumina powder, and the modified clay obtained in step (1) were mixed and stirred at 70° C. for 3 h to react. After the reaction, the obtained silicon-aluminum precursor (silicon-aluminum molar ratio of about 1:1) was placed in a constant temperature and humidity drying oven, 162.10 g of ferric nitrate nonahydrate was added, and aged at 70° C. for 5 h. The temperature was then raised to 90° C. for crystallization for 16 h. Filtered to obtain 431 g of a wet product, which was washed to neutrality.

[0065] (3) 257 g of alumina powder and 18 g of sodium hydroxide were mixed evenly to obtain modified alumina.

[0066] (4) The modified alumina, the wet product obtained in (2), and 16.2 g of sesbania powder (accounting for 8.19% of the mass of the modified alumina) were mixed, water was added to adjust the material moisture content to about 30%, and the mixture was rolled into balls, dried at 120° C. for 2 h, and calcined at 380° C. for 3 h to obtain a desulfurization and dehydration catalyst with a particle size of 2 to 3 mm. Among them, iron accounted for 4.16% of the mass of the desulfurization and dehydration catalyst.

[0067] Example 4

[0068] This embodiment provides a desulfurization and dehydration catalyst and a preparation method thereof, comprising the following steps:

[0069] (1) 50 g of sodium bicarbonate and 300 g of diatomaceous earth were mixed and calcined at 350° C. for 2 h to obtain modified clay.

[0070] (2) 300 mL of 3 mol / L sodium hydroxide solution, 364 g of alumina powder, and the modified clay obtained in step (1) were mixed and stirred at 70° C. for 3 h to react. After the reaction, the obtained silicon-aluminum precursor (silicon-aluminum molar ratio of about 1:1) was placed in a constant temperature and humidity drying oven, 164.20 g of cobalt nitrate hexahydrate was added, and aged at 70° C. for 5 h. The temperature was then raised to 90° C. for crystallization for 16 h. The mixture was filtered to obtain 625 g of a wet product, which was washed to neutrality.

[0071] (3) 386 g of alumina powder and 27 g of sodium hydroxide were mixed uniformly to obtain modified alumina.

[0072] (4) The modified alumina, the wet product obtained in (2), and 24.3 g of sesbania powder (accounting for 8.18% of the mass of the modified alumina) were mixed, water was added to adjust the material moisture content to about 30%, and the mixture was rolled into balls, dried at 120° C. for 2 h, and calcined at 380° C. for 3 h to obtain a desulfurization and dehydration catalyst with a particle size of 2 to 3 mm. Among them, cobalt accounts for 4.11% of the mass of the desulfurization and dehydration catalyst.

[0073] Example 5

[0074] This embodiment provides a desulfurization and dehydration catalyst and a preparation method thereof, comprising the following steps:

[0075] (1) 50 g of sodium bicarbonate and 300 g of attapulgite were mixed and calcined at 350° C. for 2 h to obtain modified clay.

[0076] (2) 300 mL of 3 mol / L sodium hydroxide solution, 206 g of alumina powder, and the modified clay obtained in step (1) were mixed and stirred at 70° C. for 3 h to react. After the reaction, the obtained silicon-aluminum precursor (silicon-aluminum molar ratio of about 1:1) was placed in a constant temperature and humidity drying oven, 81.91 g of copper nitrate trihydrate was added, and aged at 70° C. for 5 h. The temperature was then raised to 90° C. for crystallization for 16 h, and filtered to obtain 434 g of a wet product, which was washed to neutrality.

[0077] (3) 249 g of alumina powder and 17.4 g of sodium hydroxide were mixed uniformly to obtain modified alumina.

[0078] (4) The modified alumina, the wet product obtained in (2), and 15.67 g of sesbania powder (accounting for 8.17% of the mass of the modified alumina) were mixed, water was added to adjust the material moisture content to about 30%, and the mixture was rolled into balls, dried at 120° C. for 2 h, and calcined at 380° C. for 3 h to obtain a desulfurization and dehydration catalyst with a particle size of 2 to 3 mm. Among them, copper accounted for 4.15% of the mass of the desulfurization and dehydration catalyst.

[0079] Example 6

[0080] This embodiment provides a desulfurization and dehydration catalyst and a preparation method thereof, comprising the following steps:

[0081] (1) 50 g of sodium hydroxide and 250 g of kaolin were mixed and calcined at 400° C. for 2 h to obtain modified clay.

[0082] (2) 275 mL of 5 mol / L sodium hydroxide solution, 186 g of alumina powder, and the modified clay obtained in step (1) were mixed and stirred at 80° C. for 2 h to react. After the reaction was completed, the obtained silicon-aluminum precursor (silicon-aluminum molar ratio of about 1:1) was placed in a constant temperature and humidity drying oven, 78.25 g of copper nitrate trihydrate was added, and aged at 80° C. for 4 h. The temperature was then raised to 110° C. for crystallization for 12 h, and filtered to obtain 363 g of a wet product, which was washed to neutrality.

[0083] (3) 238 g of alumina powder and 18 g of sodium hydroxide were mixed evenly to obtain modified alumina.

[0084] (4) The modified alumina, the wet product obtained in (2), and 31 g of grass powder (accounting for 16.79% of the mass of the modified alumina) were mixed, water was added to adjust the material moisture content to about 30%, and the mixture was rolled into balls, dried at 120° C. for 2 h, and calcined at 400° C. for 2 h to obtain a desulfurization and dehydration catalyst with a particle size of 2 to 3 mm. Among them, copper accounts for 4.14% of the mass of the desulfurization and dehydration catalyst.

[0085] Example 7

[0086] This embodiment provides a desulfurization and dehydration catalyst and a preparation method thereof, comprising the following steps:

[0087] (1) 50 g of sodium hydroxide and 350 g of kaolin were mixed and calcined at 300° C. for 3 h to obtain modified clay.

[0088] (2) 320 mL of 1 mol / L sodium hydroxide solution, 186 g of alumina powder, and the modified clay obtained in step (1) were mixed and stirred at 60° C. for 4 h to react. After the reaction was completed, the obtained silicon-aluminum precursor (silicon-aluminum molar ratio of about 1:1) was placed in a constant temperature and humidity drying oven, 109.66 g of copper nitrate trihydrate was added, and the mixture was aged at 60° C. for 6 h, then the temperature was raised to 80° C. for crystallization for 20 h, and filtered to obtain 520 g of a wet product, which was washed to neutrality.

[0089] (3) 335 g of alumina powder and 22 g of sodium hydroxide were mixed evenly to obtain modified alumina.

[0090] (4) The modified alumina, the wet product obtained in (2), and 12.5 g of grass powder (accounting for 4.87% of the mass of the modified alumina) were mixed, water was added to adjust the material moisture content to about 30%, and the mixture was rolled into balls, dried at 90° C. for 3 h, and calcined at 350° C. for 4 h to obtain a desulfurization and dehydration catalyst with a particle size of 2 to 3 mm. Among them, copper accounts for 4.13% of the mass of the desulfurization and dehydration catalyst.

[0091] Comparative Example 1

[0092] This comparative example provides a desulfurization and dehydration catalyst and a preparation method thereof. The difference from Example 1 is that copper nitrate trihydrate is not added in step (2).

[0093] Comparative Example 2

[0094] The present comparative example provides a desulfurization and dehydration catalyst and a preparation method thereof. Compared with Example 1, the difference is that copper nitrate trihydrate is not added in step (2), and the following steps are included after step (4): 60.5 g of copper nitrate trihydrate is taken to prepare a 0.1 mol / L copper nitrate solution, and the product obtained in step (4) is added at 60° C., ion exchange is performed for 8 h, drying is performed at 120° C. for 2 h, and roasting is performed at 380° C. for 3 h to obtain a desulfurization and dehydration catalyst.

[0095] In comparative example 2, a catalyst having formed pores and not containing transition metals is first prepared, and then a desulfurization and dehydration catalyst is obtained by ion exchange. Compared with the preparation method in the embodiment, the number of steps is increased, and the cost of producing 1 t of desulfurization and dehydration catalyst increases by 3,000 to 5,000 yuan.

[0096] Test Example 1

[0097] The pore size distribution diagram of the desulfurization and dehydration catalyst obtained in Example 1 was tested using the nitrogen adsorption method (refer to GB / T 19587-2017). Figure 1 shown.

[0098] The pore size distribution diagram of the desulfurization and dehydration catalyst obtained in Comparative Example 2 was tested using the nitrogen adsorption method (refer to GB / T 19587-2017). Figure 2 As shown, it can be seen that under nitrogen atmosphere conditions, the pore size cannot be detected, indicating that the pores of the material are smaller than the running diameter of nitrogen. After transition metal ion exchange, the pores of the material are blocked.

[0099] TEM image of the final product of Test Example 1, as shown Figure 3 As shown. Combined Figure 1 , Figure 3 It can be seen that the desulfurization and dehydration catalyst prepared in the present invention does have a dual pore structure of mesopores and micropores.

[0100] Test Example 2

[0101] The desulfurization and dehydration catalysts prepared in the examples and comparative examples were tested for their specific surface area and pore volume using a physical adsorption instrument (model ASAP2460, Micromeritics Instruments, USA), and the results are shown in Table 1. It can be seen that compared with comparative example 1, although the transition metal is combined in the examples, the specific surface area and pore volume are still relatively high, and the dehydration effect can be effectively exerted.

[0102] Table 1

[0103] sample <![CDATA[Specific surface area m 2 / g]]> <![CDATA[Pore volume cm 3 / g]]> Example 1 369.34 0.35 Example 2 366.31 0.34 Example 3 367.45 0.33 Example 4 369.11 0.34 Example 5 368.80 0.33 Example 6 361.96 0.31 Example 7 360.78 0.32 Comparative Example 1 395.63 0.32

[0104] Test Example 3

[0105] The desulfurization and dehydration catalysts prepared in the examples and comparative examples were tested for their activity.

[0106] Test conditions: Raw gas: propane: 33%, propylene, 17%, hydrogen sulfide 1500ppm, water 500ppm, hydrogen as balance gas; dosage 10ml; space velocity 1000h -1 ; The temperature is 40°C. After the sulfur capacity is evaluated to be greater than 1% and the water capacity is 0.2%, the desulfurization and dehydration catalysts are regenerated at 230°C in a hydrogen atmosphere; and then the activity test is continued under the above test conditions. The number of regenerations can be recorded; the standard for successful regeneration is: the regenerated catalyst is tested for activity under the above test conditions, and the accuracy of sulfide and water detected at the outlet is consistent with that at the initial use.

[0107] Test method: Agilent gas chromatograph and water content analyzer are used at the outlet to test the hydrogen sulfide outlet accuracy and water outlet accuracy respectively.

[0108] The test results are shown in Table 2.

[0109] Table 2

[0110]

[0111] According to actual working conditions, the desulfurization and dehydration catalyst can be regenerated 183 times a year to meet the use requirements. As can be seen from Table 2, the desulfurization and dehydration catalyst prepared in the embodiment of the present invention has a regeneration frequency of >200 times, and the water accuracy and hydrogen sulfide accuracy at the outlet are both 0ppm, which can meet the actual use conditions. However, the desulfurization and dehydration catalyst prepared in Comparative Example 1 has a hydrogen sulfide outlet accuracy of 0.1ppm and a regeneration frequency of <50 times, which cannot meet the actual use conditions.

[0112] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A method for preparing a desulfurization and dehydration catalyst, characterized in that: The steps include: S1: mixing alkaline substances and clay, and calcining to obtain modified clay; S2: mixing alkali solution, alumina and modified clay, reacting, adding soluble transition metal salt to the obtained silicon-aluminum precursor, aging, crystallizing, and solid-liquid separation to obtain a wet product; S3: mixing alumina and alkaline substances to obtain modified alumina; S4: Mix the modified alumina, wet product and additives, granulate, dry and calcine to obtain a desulfurization and dehydration catalyst.

2. The preparation method according to claim 1, characterized in that: In the step S1, the calcination temperature is 300-400°C and the calcination time is 2-3 hours.

3. The preparation method according to claim 1 or 2, characterized in that: In S2, the reaction temperature is 60-80°C and the reaction time is 2-4h; And / or, in S2, the reaction is carried out under stirring.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In S2, the aging temperature is 60-80°C and the time is 4-6h; And / or, in S2, the crystallization temperature is 80-100° C. and the time is 12-20 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In S4, the drying temperature is 90-120°C and the drying time is 2-3h; And / or, in S4, the calcination temperature is 350-400° C. and the calcination time is 2-4 hours.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In said S1, the mass ratio of clay to alkaline substance is 5:1 to 7:1; And / or, in S2, the molar ratio of silicon to aluminum in the silicon-aluminum precursor is 1:0.9-1.1; and / or, the liquid-to-solid volume mass ratio of the alkali solution to the clay is 1 mL: 0.9-1.1 g; optionally, the concentration of the alkali solution is 1-5 mol / L; And / or, in S3, the mass ratio of aluminum oxide to alkaline substance is 9:1 to 15:1; And / or, in S4, the mass ratio of modified alumina to wet product is 1:1-3; and / or, the mass of the soluble transition metal accounts for 3% to 6% of the mass of the desulfurization and dehydration catalyst; And / or, the mass of the auxiliary agent is 4% to 17% of the mass of the modified alumina.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The granulation method includes ball forming.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The clay includes at least one of bentonite, kaolin, montmorillonite, diatomaceous earth and attapulgite; And / or, the alkaline substance includes at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate; And / or, the alkali solution includes at least one of a sodium hydroxide solution, a sodium carbonate solution, and a sodium bicarbonate solution; And / or, the soluble transition metal salt includes at least one of copper nitrate, iron nitrate, cobalt nitrate, copper sulfate, iron sulfate, and cobalt sulfate; and / or, the auxiliary agent comprises at least one of carboxymethyl cellulose, sesbania powder, and grass powder; And / or, the alumina is macroporous alumina; optionally, the pore volume of the macroporous alumina is ≥0.8cm 3 / g, average pore size ≥10nm; Optionally, the pore volume of the macroporous alumina is 0.8cm 3 / g~1.2cm 3 / g, and the average pore size is 10-30nm.

9. A desulfurization and dehydration catalyst prepared by the preparation method according to any one of claims 1 to 8; optionally, the particle size of the desulfurization and dehydration catalyst is 1.5 to 5 mm.

10. Use of the desulfurization and dehydration catalyst as claimed in claim 9 in a propylene preparation process.